VERBA TO EXPECT DALAM BAHASA INGGRIS DAN LEKSIKON PADANANNYA DALAM BAHASA INDONESIA: SUATU KAJIAN METABAHASA SEMANTIK ALAMI - , ENI MAHARSI, Dr. Suhandano, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This corpus-based study investigates verbs relating to mental attitude of expecting in English and its lexical equivalents in Indonesian through the framework of Natural Semantic Metalanguage (hereafter NSM). The objectives are (i) to describe the lexical equivalents of English verb to expect in Indonesian